2017
DOI: 10.1007/s00439-017-1809-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep intronic mutations and human disease

Abstract: Next-generation sequencing has revolutionized clinical diagnostic testing. Yet, for a substantial proportion of patients, sequence information restricted to exons and exon-intron boundaries fails to identify the genetic cause of the disease. Here we review evidence from mRNA analysis and entire genomic sequencing indicating that pathogenic mutations can occur deep within the introns of over 75 disease-associated genes. Deleterious DNA variants located more than 100 base pairs away from exon-intron junctions mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
300
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(322 citation statements)
references
References 258 publications
5
300
0
Order By: Relevance
“…The 3 patients carried an homozygous deep intronic variation (i.e. >100 bases from the exon-introns boundaries) (Vaz-Drago et al, 2017) with a predicted splicing effect on the PSMC3 gene that we confirmed on the patient's cells. We then focused on demonstrating the effect of this variation at the level of the proteasome.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The 3 patients carried an homozygous deep intronic variation (i.e. >100 bases from the exon-introns boundaries) (Vaz-Drago et al, 2017) with a predicted splicing effect on the PSMC3 gene that we confirmed on the patient's cells. We then focused on demonstrating the effect of this variation at the level of the proteasome.…”
Section: Discussionsupporting
confidence: 61%
“…Sequencing the entire genome of patients gives access to the whole spectrum of their variations and possibly disease causing ones. WGS is a powerful tool (Belkadi et al, 2015) helping to identify variations not covered or missed by WES such as structural variations (Geoffroy et al, 2018b) or deep intronic variations (Vaz-Drago et al, 2017). Interestingly, in this study, we combined to WGS, homozygosity mapping and in silico predicted interactors to narrow down to the region of PSMC3.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, information of known units of functional DNA sequences, such as promoters and enhancers, molecular ‘tags’ marking active/repressive status of these elements (such as histone marks and DNA methylation), and various bioinformatics tools and databases to predict functionality of genomic regions and variants in these regions can be utilized. Before describing findings in studies aiming to uncover roles of rare non‐coding variants in specific diseases, an overview of representative functional non‐coding regulatory elements, their molecular indicators, and technologies to identify them are presented in Table and Figures …”
Section: Rapidly Expanding Knowledge On Functional Non‐coding Elementsmentioning
confidence: 99%
“…The term exome refers to the sequence of all exons of all protein coding genes, and encompasses approximately 1–2% of the genome, but bears an estimated 85% of mutations that cause Mendelian disorders . Some diseases are associated with deep intronic mutations …”
Section: Overview Of Geneticsmentioning
confidence: 99%
“…11 Some diseases are associated with deep intronic mutations. 12 Protein Synthesis. Protein synthesis, regulated by ribonucleic acid (RNA), involves two steps: transcription and translation.…”
Section: Overview Of Geneticsmentioning
confidence: 99%